Aproximações entre as comunidades científica, amadora e escolar: estudando as potencialidades de observatórios astronômicos para a educação em astronomia - Langhi, Rodolfo [UNESP]; Scalvi, Rosa Maria Fernandes [UNESP] (My University, 2013)
This article considers some potential of activities developed in non-formal education in astronomy, like astronomical observatories and other related establishments. This kind of research is less explored in our country. We present, in this text, a model to study possible relations among these kinds of communities: the scientific, the amateur and the professional, applicable in astronomical observatories, in a motion against the local and punctual activities dispersion and pulverization of these establishments, and against the use of common sense to develop their activities, aiming the advancement of the astronomy education and its national research.

Este artigo considera brevemente algumas das potencialidades, ainda pouco exploradas em nosso país, referentes às atividades desenvolvidas em ambientes não escolares de ensino de astronomia, tais como os observatórios astronômicos e demais estabelecimentos relacionados. Apresentamos um modelo que aborda aproximações possíveis entre as comunidades científica, amadora e profissional, aplicáveis em observatórios astronômicos, seguindo um movimento de sentido contrário à dispersão e pulverização de esforços pontuais destes estabelecimentos e da realização de suas atividades embasadas no senso comum, visando o desenvolvimento nacional da educação em astronomia e de sua pesquisa.
Approaches between the scientific, amateur and school communities: studying the potential of astronomical observatories for astronomy education
Keywords: Astronomy education; Teacher formation; Relations among scientific; Amateur and professional communities; Astronomical observatory; Scientific popularization; Educação em astronomia; Formação de professores; Relações comunidade científica/ amadora/escolar; Observatório astronômico; Divulgação científica